A review of 31 cases of Marjolin's ulcer on scalp: Is it necessary to preventively remove the scar?. Issue 2 (26th December 2018) - Xiao, Haitao; Deng, Ke; Liu, Ruolin; Chen, Zihang; Lin, Yun; Gao, Yuan; Cen, Ying; Xu, Xuewen
Abstract : We aimed to report the clinical features of squamous cell carcinoma (SCC) occurring on scalp scar tissue among a Chinese population, demonstrate its pathological progress, analyse the prognosis‐related factors, and share our clinical experience of managing this rare disease in practice. A retrospective study was conducted at West China Hospital from January 2013 to January 2018 aiming to identify patients with a diagnosis of SCC or squamous atypical hyperplasia arising from scalp scars. Their medical records were reviewed, and related data were retrieved. Follow up was conducted, and informed consent was obtained by phone calls in June 2018. Of the 31 scalp Marjolin's ulcer (MU) patients, the average latency period and post‐ulceration period were 42.9 years and 37.5 months, respectively. Among them, 30 patients (97%) were diagnosed with cancer more than 5 years after initial injury, and 25 patients (80.7%) experienced a pre‐ulceration period longer than 20 years. A negative correlation between scalp MU's post‐ulceration period and its pre‐ulceration period was identified. Only burn scars caused post‐ulceration periods of more than 24 months (7/19). Incomplete healing wounds experienced a significantly shorter latency period ( P = 0.004) and longer post‐ulceration period than others ( P < 0.0001). However, the depth of tumour infiltration and complete tumour resection were the only two independent factors that significantly dictated patients' survival in this study. In conclusion, the scalp scaring tissue experienced a long‐term stable period but would transform to malignancy rapidly and progressively once ulceration formed. The underlying malignant transformation mechanism remains unclear. Thus, we recommend scalp scarring tissue to be radically removed.